The Development of General Functional Civil Servant Competency Model: The Case of Group III Non Job (Executor) in KODIKLATAL - Imam Danu Pranoto; Suryanto Suryanto (Research Synergy Foundation, 2022)
Human resources are a very important asset for Kodiklatal as an educational and training institution for the Indonesia Navy, so work professionalism is needed to create superior human resources. The impact that arises with low competence can affect organizational work productivity to decrease. The development of an effective civil servant competency model greatly influences civil servants in increasing work productivity. This study aims to describe the problems of PNS Group III Nonjob by developing an effective competency model and knowing the factors that cause problems. This research uses qualitative with narrative method which is conveyed by the main informant as many as 4 people and the key informant 1 person. Data analysis method with data triangulation. The results of the study indicate that the development of the current competency model with education and training needs to be supported by managerial competence, technical competence and socio-cultural competence so as to increase motivation, Self Concept, Self Convidence and Self Problem. The resistance that arises related to career development is due to the rejection factor that comes from the individual, Emotional rejection, Denial of comfort, Rejection due to differences in perception/point of view, Rejection influenced by the environment/external factors. The limitation of this research is the regulation of the rules for developing competency models with education, training and leadership that have been determined by the government. This research was conducted with the novelty of the rejection in the competency development model that aims at individual career development.